Perencanaan Sistem Ventilasi Pada Tambang Batubara Bawah Tanah Seam C2 Di PT. Nusa Alam Letari, Desa Salak, Kecamatan Talawi, Kota Sawahlunto, Sumatera Barat. - Rizka Sestiana; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. PT. Nusa Alam Lestari is one of the mining companies engaged in coal mining located in the Village of Salak, Talawi District, Sawahlunto City, West Sumatra. Mining activities carried out by PT. Nusa Alam Lestari was initially carried out with open pit mines and underground mines. However, since 2011 no open pit mining has been carried out due to the lack of economic coal mining (higher SR). So that currently mining is only done with underground mining. With the room and pillar mining method. PT. Nusa Alam Lestari has several seam coal reserves including the C1 seam, which ended its mining period in December 2017, because of that, it was followed by seam mining C2. As for the ventilation system used is the suction system (exhaus system) with the arrangement of blower relay. Installation of the suction blower system is followed by the installation of blowers, so that dirty air is immediately circulated out. Dirty air resulting from mining activities from one suction hole comes out through the ventilation hole and then changes with clean air entering through the other hole. The total air requirement for mining activities in C2 A seam is 686.6264 m3 / s, and in C2 B seam is 686.6264 m3 / s. . The number of blowers used to support 13 panels will be carried out development and 53 crosscut, then ventilation control is required by installing 13 auxiliary blowers on each panel with a diameter of 20 "(37 KW), and to release dirty air out, 6 main Suction blower fans will be installed 32 "(75 KW) in diameter.Modeling of the ventilation system using Ventsim visual 3 and producing a 3D ventilation system modelKeywords: Undergraound mines, Ventilation, Blower, Exhaus System, Modeling.